Prostaglandin E2 Indicates Therapeutic Efficacy of Mesenchymal Stem Cells in Experimental Traumatic Brain Injury. (16th March 2017) - Kota, Daniel J.; Prabhakara, Karthik S.; Toledano-Furman, Naama; Bhattarai, Deepa; Chen, Qingzheng; DiCarlo, Bryan; Smith, Philippa; Triolo, Fabio; Wenzel, Pamela L.; Cox, Charles S.; Olson, Scott D.
Abstract : Traumatic brain injury (TBI) is soon predicted to become the third leading cause of death and disability worldwide. After the primary injury, a complex set of secondary injuries develops hours and days later with prolonged neuroinflammation playing a key role. TBI and other inflammatory conditions are currently being treated in preclinical and clinical trials by a number of cellular therapies. Mesenchymal stem cells (MSC) are of great interest due to their widespread usage, safety, and relative ease to isolate and culture. However, there has been a wide range in efficacy reported using MSC clinically and in preclinical models, likely due to differences in cell preparations and a significant amount of donor variability. In this study, we seek to find a correlation between in vitro activity and in vivo efficacy. We designed assays to explore the responsiveness of MSC to immunological cues to address the immunomodulatory properties of MSC, one of their primary modes of therapeutic activity in TBI. Our results showed intrinsic differences in the immunomodulatory capacity of MSC preparations from different bone marrow and amniotic fluid donors. This difference mirrored the therapeutic capacity of the MSC in an experimental model of TBI, an effect confirmed using siRNA knockdown of COX2 followed by overexpressing COX2 . Among the immunomodulatory factors assessed, the therapeutic benefit correlated with the secretion of prostaglandin E2 (PGE2 ) by MSC prior to treatment, suggesting that measurement of PGE2 could be a very useful potency marker to create an index of predicted efficacy for preparations of MSC to treat TBI.